Development of odorless cassava-based ‘fufu’ with mixed starter cultures through a fermentation process and characterization of its functional, chemical properties and sensory qualities - Catherine Yemisi Babatuyi; Esther Bola Boboye; Tayo Nathaniel Fagbemi (Discover Food)
Abstract The quest for satiable odourless ‘fufu’ meal as a substitute to ‘garri’ or change in meal have been the request of researchers. ‘Fufu’ is starchy based food with objectionable odour released during fermentation as a result of activities of some microbial metabolites. It is highly desirable dough meal but limited by the undesirable and offensive odour made from the cassava mash. Therefore, this research aimed at studying the development and assessment of odourless ‘fufu’ alongside its chemical composition and sensory quality. Freshly harvested cassava roots were peeled washed and cleaned, and cut into three sections. A portion was simply grated without inoculum (CW). A section was grated, blanched for 15 min at 65 °C, and added with the six (6) groups of pure isolates. They were Bacteria (BA), Yeast & Bacteria (BY), Yeast (YA), Mould & Bacteria (BM), Yeast & Mould (MY), and Mould (MA). The final quantity was chopped into 3 to 4 cm length, immersed in sterile water (SW) to make eight samples. The samples were allowed to ferment for 72 h. The samples were made into ‘fufu’. The physicochemical values were evaluated. There was steady increase in microbial load in all the media used during the fermentation period, having population of LAB (Lactic Acid Bacteria) being the most highest load (1.93 × 107 cfu/g) that contributed to the acidification of the ‘fufu’ within 72 h of fermentation. The bulk density, swelling index, oil & water absorption capacities rise from 0.588 gm3 to 0.769 ml, 0.1 to 2.2 ml, 125% to 214% and 300 to 580%. The ‘fufu’ whiteness of the samples were affected by starter cultures in samples MY (59%) and MA (68.2%). Pasting characteristics favours samples CW, BA, BY and YA. The sensory qualities of the samples MY and MA had least acceptance.